Cesaŕo Summable Relative Uniform Difference Sequence of Positive Linear Functions. (27th April 2022) - Bakery, Awad A.; Mohamed, O. M. Kalthum S. K.; Devi, Kshetrimayum Renubebeta; Tripathy, Binod Chandra
Abstract : In this article, we introduce the class of sequence of functions C 1 Δ, r u of Cesaŕo summable relative uniform difference sequence of functions. We have studied the topological properties of C 1 Δ, r u . We also obtain the necessary and sufficient condition to characterize the matrix classes C 1 Δ, r u, ℓ ∞ r u, C 1 Δ, r u, c r u, P .